Fresh Cadaver Simulation Model with Continuous Extracorporeal Circulation as a Training Platform for Intracranial High-Flow Bypass: Technical Note and Rheologic Feasibility Evaluation - Santori, Alejandro Mercado; Arancibia, María Sol; Andaluz, Norberto (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction As endovascular techniques evolve toward replacing open surgery, several clinical scenarios still require surgical revascularization. Characterizing this era are decreasing surgical volumes and lack of realistic training models. In an effort to develop lifelike simulation models, we developed a platform for surgical training on high-flow bypass in a fresh cadaver model. Our technique incorporated an extracorporeal circulating system that resembled clinical conditions and confirmed anastomosis efficacy by clinical parameters.Methods On three fresh cadaveric heads, the subtemporal approach exposed the petrous internal carotid artery (ICA) (C2) as the donor vessel for an interposition radial artery graft. Using a continuous extracorporeal circulation system, the bypass model was tested in three fresh heads and verified using clinical technologies.Results Successful C2 ICA to M2 anastomosis was completed in all three fresh heads, confirmed with qualitative and quantitative Doppler, and indocyanine green angiography. Antegrade distribution through graft and revascularized territory was documented on postoperative computed tomography (CT) scan with radiopaque silicone injected through the ipsilateral carotid.Conclusion This study confirmed the feasibility of a totally intracranial high-flow bypass in a fresh cadaver model that achieved hemodynamic features aligned with those of normal middle cerebral artery flow in the clinical setting.
Keywords: cerebral revascularization; high-flow bypass; simulation training; middle fossa